2017
DOI: 10.1177/1074840717697436
|View full text |Cite
|
Sign up to set email alerts
|

From Feeling Broken to Looking Beyond Broken: Palestinian Mothers’ Experiences of Having a Child With Spina Bifida

Abstract: Spina bifida (SB) is the second most common birth defect worldwide. Mothers of children with SB face extraordinary challenges due to the complicated conditions and disability of their children. Little is known about the impact of these challenges on the mothers' well-being, particularly in Middle Eastern culture, where chronic illness and disability are perceived as a stigma, and care of disabled children has traditionally been the responsibility of the mother. The aim of this study was to illuminate mothers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…At the mezzo level, our results are similar to other studies conducted in different Arab and non-Arab countries (Manor-Binyamini & Abu-Ajaj, 2017) and the United States (Ambikile & Outwater, 2012; Azaiza et al, 2006; Daire et al, 2011; Green, 2004; Nahal et al, 2017), particularly, late and inaccurate diagnosis of children with autism spectrum disorder. Williams and Brayne (2006) argue that based on current research and existing measures, early screening for autism spectrum disorders before 2 years is still not conceivable.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…At the mezzo level, our results are similar to other studies conducted in different Arab and non-Arab countries (Manor-Binyamini & Abu-Ajaj, 2017) and the United States (Ambikile & Outwater, 2012; Azaiza et al, 2006; Daire et al, 2011; Green, 2004; Nahal et al, 2017), particularly, late and inaccurate diagnosis of children with autism spectrum disorder. Williams and Brayne (2006) argue that based on current research and existing measures, early screening for autism spectrum disorders before 2 years is still not conceivable.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, they were confused and frustrated and recognized that the lack of information delayed their ability to address their children’s special needs in a timely manner. These findings were mirrored in Nahal et al’s (2017) study of mothers with children with spina bifida in the West Bank. Some mothers reported that medical providers were not empathetic and too direct when sharing the child’s diagnosis, which in turn, intensified their fears and worries.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although, to date, there are no studies on LD stigma in the Israeli Arab society, research shows that people with disabilities are generally stigmatized in Arab societies in Israel and elsewhere (e.g., see Abu-Ras et al, 2018; Al-Aoufi et al, 2012; Al-Thani, 2006; Bazna & Hatab, 2005; Dolev et al, 2016; Gharaibeh, 2009; Nahal et al, 2017). Research shows that Arab families who have a child with a disability tend to experience social embarrassment and shame, and to fear—and experience—social exclusion (Al-Aoufi et al, 2012; Alsayyari, 2017; Dolev et al, 2016; Sandler-Loeff & Shahak, 2006).…”
mentioning
confidence: 99%
“…Arab women are expected to fulfill traditional roles associated with femininity, that is, being a wife and a mother (Alsayyari, 2017; Haj-Yahia, 2003). This also entails being the primary caregiver for children with disabilities (Nahal et al, 2017). Research has shown that, compared with Western societies, in Arab societies children are entrusted entirely to the mother in the first 7 to 9 years of their lives.…”
mentioning
confidence: 99%